Determinants Influence the Incidence of Stunting in Toddlers Aged 6-59 Months - Herlianty Herlianty; Ari Setyawati; Anita Lontaan; Theresia Limbong; Indrawati Aris Tyarini; Sitti Zakiyyah Putri (Jurnal Edukasi Ilmiah Kesehatan, 2023)
Stunting is a serious public health problem, especially in children under five. The causes of stunting are complex and involve a variety of factors, but health education, feeding practices, attention, stimulation, and access to health services have been identified as major contributors. This study aims to determine the factors that influence the incidence of stunting in toddlers. The research design is observational analytics using a case-control research design. The results show a statistical test result value of p-value of 0.016; employment of 0.013; family income of 0.002. It can be concluded that parenting affects the incidence of stunting in toddlers. Stunting is the result of a combination of complex factors and interactions between social, economic, health, and environmental aspects. Therefore, stunting handling must also be holistic and involve various sectors to achieve optimal results. It is important for parents to provide proper attention and support in terms of nutrition, health, and stimulation of children to support optimal growth and development.